An evidence‐based review of the impact of periprocedural myocardial infarction in carotid revascularization. Issue 5 (19th July 2013) - Stilp, Erik; Baird, Colleen; Gray, William A.; Schneider, Peter A.; Simonton, Charles A.; Verta, Patrick; Mena‐Hurtado, Carlos I.
<x xml:space="preserve">Abstract</x> Landmark trials comparing carotid endarterectomy (CEA) with medical therapy in patients with symptomatic or asymptomatic atherosclerotic stenosis of extracranial carotid arteries have favored carotid revascularization. Carotid artery stenting (CAS) has emerged as a minimally invasive option for revascularization of carotid artery stenoses and has been shown to be noninferior to CEA, regardless of patient symptom status. Debate continues regarding the importance of periprocedural myocardial infarction (PMI) as an endpoint in carotid revascularization trials. Recent randomized comparisons of CEA and CAS pre‐specify PMI as an endpoint. Understanding PMI in CEA and CAS, the need for routine biomarker assessment surrounding both revascularization strategies, the effect of PMI on long‐term morbidity and mortality, and the groups most at risk for PMI are of critical importance when choosing a carotid revascularization strategy for symptomatic and asymptomatic patients, since decreasing the incidence of PMI will make revascularization safer. This review examines available data regarding the relevance of PMI in vascular and carotid‐specific outcomes. © 2013 Wiley Periodicals, Inc.